Ciri Agronomi dan Serat Delapan Varian Sorgum sebagai Pakan - Wijaya Murti Indriatama; Winda Puspitasari; Wahidin Teguh Sasongko; Yenny Nur Anggraeny; Soeranto Human; Sihono Sihono; Widhi Kurniawan; Sutiyoso Sutiyoso; Yukarie Ayu Wulandari; Teguh Wahyono (Institut Pertanian Bogor, 2023)
Sorghum is a multifunctional crop as a source of food, feed, and alternative energy. Plant breeding using the radiation mutation technique was applied to improve the characteristics of sorghum according to its purpose. This study evaluated the agronomic and fiber characteristics of selected sorghum mutant lines. Eight sorghum mutant lines were observed in this study (GHP-2, GHP-3, GHP-4, GHP-5, GHP-7, G-5, P-341, and P36.M10). Pahat and Bioguma sorghum varieties were used as control. Compared to eight selected mutant lines, Bioguma variety was the tallest plant. Except for P-341, all selected mutant sorghum lines produced lower plant biomass than Bioguma. The highest sugar content was produced by G-5 and P-36.M10. There are no significant differences in seed production per panicle. The lowest fiber fractions in the leaf and stem were produced by GHP-3 and G-5 mutant lines, respectively. Based on our findings, the P-341 sorghum mutant line can be used as forage sorghum because it produces high biomass and relatively low fiber content. The G-5 mutant line can be projected as an alternative energy source due to its high stem sugar content. Keywords: agronomy, fiber, mutant, sorghum